If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 5x = 3 Solving X + 5x = 3 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-5x' to each side of the equation. X + 5x + -5x = 3 + -5x Combine like terms: 5x + -5x = 0 X + 0 = 3 + -5x X = 3 + -5x Simplifying X = 3 + -5x
| 5x+17-4x=9+4x-7 | | x+7m=78m^2 | | 346*65=x | | 4x+7x-3x=34+6 | | -10x+(-5)-x=28 | | -10x+5-x=28 | | 34*15=x | | -3y-3=1+2y | | -9x-4=203 | | X^2+94=-2 | | 3px(-4)=6 | | 5y-4=19y+108 | | 3x-12+8x=87 | | 0=3x(x-4)(x-1) | | -x+x+30= | | 0=3x(x-4)(x-1) | | 2x-48=52 | | 2x-48=52 | | x+Bx+25=(x+5) | | 2a+3b-5a= | | 6x-4=44-2x | | 2(x-6)-9=19-6x | | 10+.3x=x-2 | | 48-2x=8x+8 | | 10+1.3x=x-2 | | 42975-125m=45000-350m | | 0.3t+-0.3t=x | | 5(2-4t)+3t=5t+7 | | 0.37(28+62.7x)=56.758 | | 11+m=9 | | 5.6x^2+40x+400=0 | | 9007-5667=x |